An estimate of amyotrophic lateral sclerosis heritability using twin data. Issue 12 (22nd September 2010) - Al-Chalabi, A; Fang, F; Hanby, M F; Leigh, P N; Shaw, C E; Ye, W; Rijsdijk, F
Abstract : Background: Causative gene mutations have been identified in about 2% of those with amyotrophic lateral sclerosis (ALS), often, but not always, when there is a strong family history. There is an assumption that there is a genetic component to all ALS, but genome-wide association studies have yet to produce a robustly replicated result. A definitive estimate of ALS heritability is therefore required to determine whether ongoing efforts to find susceptibility genes are worth while. Methods: The authors performed two twin studies, one population- and one clinic-based. The authors used structural equation modelling to perform a meta-analysis of data from these studies and an existing twin study to estimate ALS heritability, and identified 171 twin pairs in which at least one twin had ALS. Results and discussion: Five monozygotic twin pairs were concordant-affected, and 44 discordant-affected. No dizygotic twin pairs were concordant-affected, and 122 discordant-affected. The heritability of sporadic ALS was estimated as 0.61 (0.38 to 0.78) with the unshared environmental component 0.39 (0.22 to 0.62). ALS has a high heritability, and efforts to find causative genes should continue.